The Complexity of Racial Prejudice: The Importance of a Broader Perspective - Mizael, Táhcita Medrado; de Almeida, João Henrique [UNESP] (Editorial Pontificia Universidad Javeriana, 2022)
Our ability to relate stimuli and events in complex and arbitrarily applicable ways is considered a key feature of our language and cognition. However, although this ability, arbitrarily applicable relational responding (AARR), can be related to our increasingly developed technology and advancements in science, it can also allow the development of prejudiced behaviors (Barnes-Holmes et al., 2020)
La complejidad del prejuicio racial: La importancia de una perspectiva más amplia